Pembelajaran melalui Brain Based Learning dalam Pendidikan Anak Usia Dini - Nikmah, Alfu (THUFULA, 2015)
There are many innovations that have been made in education, both relating to curriculum, teaching materials, instructional media, learning model and others. Brain based learning or brain-based learning as a learning model actually has its own interesting bargaining power to be applied in the learning process ecpecially in the Early Childhood Education. Brain-based teaching and learning offers a concept to create learning oriented to the empowerment of student’s brain potential. There are three strategies that can be developed in implementation of brain based learning. First, create a learning environment that challenges students’ thinking ability. Second, creating a fun learning environment, third, create a situation of active and meaningful for students (active learning). By knowing the brain development in children, parents and teachers can apply the appropriate education and teaching to the children.